Odpowiedzi

2010-01-28T16:45:48+01:00
A) a+(a-b)=a+a-b=2a-b
b) 2x-(x+4)=[minus przed nawiasem zmienia znaki w nawiasie]=
=2x-x-4=x-4
c) 7-(-x+6)=7+x-6=x+1
d) -(x+4)+(x-5)=-x-4+x-5=-9
e) 1-(t+p)-(t-2)=1-t-p-t+2=-2t-p+3
f) -(-y+2)+(-2y-4)=y-2-2y-4=-y-6
6 5 6
2010-01-28T16:47:19+01:00
A) a+(a-b)
= a + a - b
= 2 a - b

b) 2x-(x+4)
= 2x - x - 4
= x - 4

c) 7-(-x+6)
= 7 + x - 6
= 1 + x

d) -(x+4)+(x-5)
= - x - 4 + x - 5
= - 9

e) 1-(t+p)-(t-2)
= 1 - t - p - t + 2
= 3 - 2t - p

f) -(-y+2)+(-2y-4)
= y - 2 - 2y - 4
= - y - 6
2 3 2
2010-01-28T17:56:15+01:00
A) a+(a-b)=a+a-b= 2a-b

b) 2x-(x+4)=2x-x-4=x-4

c) 7-(-x+6)=7+x-6=1+x

d) -(x+4)+(x-5)=-x-4+x-5=-9

e) 1-(t+p)-(t-2)=1-t-p-t+2=3-2t-p

f) -(-y+2)+(-2y-4)=y-2-2y-4=y-6
1 1 1